Exploring the Distribution, Morphology, Habitat Utilization and Taxonomic Position of Herpeto Diversity of District Buner, KP - Basit, Abdul; Saeed, Kausar; Adnan,; Ahmad, Naseer; Ubaid ur Rahman,; Ali, Arshad; Sajjad Ullah,; Said, Hameed; Ahmad, Kashif; Ali Khan, Imad; Ali, Fawad (Indus Journal of Bioscience Research, 2024)
The study was conducted from September 2019 to September 2020 and was the first attempt on the Herpeto Fauna of District Buner. We have reported 37 species of Herpeto fauna including 5 Amphibians species and 32 Reptilian species. The Amphibians includes Duttaphrynus melanostictus (Schneider, 1799), Duttaphrynus stomaticus (Lutken, 1864), Euphlyctis cyanophlyctis (Schneider, 1799), Hoplobatrachus tigurinus(Daudin, 1803) and Sphaerotheca breviceps (Schneider, 1799). The Reptiles include (Aspideretes gangeticus (Cuvier, 1825), Calotes versicolor (Daudin,1802), Laudakia badakhshan (Anderson and Leviton, 1969), Laudakia himalyana(Steindachner,1869), Laudakia nuristanica (Anderson and Leviton, 1969), Laudakia pakistanica(Baig, 1989), Eublepharis macularius (Blyth, 1854), Agamura persica (Dumeril, 1856), Cyrtopodion kachhense (Stoliczka, 1872), Cyrtopodion potoharense (Khan, 2001), Hemidactylus brookii (Gray, 1845), Hemidactylus flaviviridis(Ruppell, 1835), Hemidactylus leschenaultii (Dumeril and Bibron, 1836), Mesalina watsonana(Stoliczka, 1872), Ophisops jerdonii(Blyth, 1853), Ablepharus grayanus(Stoliczka, 1872), Eutropis dissimilis (Hallowel, 1860), Scincella Himalayana (Gunther, 1864), Eurylepis taeniolatus(Blyth, 1854), Varanus bengalensis(Daudin, 1802), Varanus flavescens(Hardwicke and Gray 1827), Amphiesma stolatum(Linnaeus, 1758), Lycodon striatus (Shaw, 1802), Oligodon arnensis (Shaw, 1802), Platyceps rhodorachis(Jan, 1865), Platyceps ventromaculatus (Gray and Hardwicke, 1834), Ptyas mucosus(Linnaeus, 1758), Spalerosophis schirazianus(Jan, 1865), Xenochrophis piscator(Schneider, 1799), Bungarus caeruleus(Schneider, 1801), Naja oxiana(Eichwald, 1831) and Echis carinatus (Schneider, 1820).In the current research the turtle Aspideretes gangeticus was first time reported from Ghurghushtu tehsil Khudokhail District Buner. Natural zone was dominant ecological zone on species richness leading by cultivated zone however urban zone have the least species richness.